Effect of frozen storage of minced meat from Indian oil sardine (Sardinella longiceps) on sausage quality - Ravisankar, C N; Shetty, T M R; Shetty, T S (Indian Journal of Fisheries, 2011)
The effect of frozen storage of minced meat from Indian oil sardine (Sardinella longicepsValenciennes) on the sausage quality was evaluated. The minced meat was given 4 different treatments —washing with chilled water and washing with solutions of sodium bicarbonate, hydrogen peroxide andsodium hypochlorite separately, followed by chilled water washing. The quality of sausages prepared fromthe samples of each treatment (control and treated with additives such as sugar, tripolyphosphate, Bl IB andBHT) drawn on each month were studied. The sausages prepared from water-washed and sodiumbicarbonate-treated minced meat + additives gave the best results compared with other treatments. The meattreated with additives was acceptable for 4 months for the preparation of sausages